2002
DOI: 10.1177/147130120200100303
|View full text |Cite
|
Sign up to set email alerts
|

Developing Awareness about Awareness in Early-Stage Dementia

Abstract: Unawareness in dementia is often viewed as a ‘symptom’ that is wholly or primarily the product of biological factors. While neurological damage may be sufficient to produce unawareness in some disorders, it is argued that this is not generally the case in early-stage dementia. Instead, it is suggested that the apparent degree of awareness is an expression of adaptive psychological responses constructed in a social situation in the context of neurologically based cognitive impairment. Drawing on examples from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 33 publications
9
108
0
5
Order By: Relevance
“…In this regard, metamemory research has shown that in AD there is reduced awareness of performance during memory tasks, with frequent overestimation of abilities (for a review, see Souchay, 2007). In addition, deficits in estimation of performance have been shown using a number of different paradigms and cognitive tasks (e.g., Agnew & Morris, 1998;Clare, 2002;Hannesdottir & Morris, 2007. This deficit in error monitoring and metacognitive ability may have a considerable impact on how an individual adapts to difficulties and performs activities of daily living (Bettcher, Giovannetti, Macmullen & Libon, 2008;Giovannetti, Libon & Hart, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, metamemory research has shown that in AD there is reduced awareness of performance during memory tasks, with frequent overestimation of abilities (for a review, see Souchay, 2007). In addition, deficits in estimation of performance have been shown using a number of different paradigms and cognitive tasks (e.g., Agnew & Morris, 1998;Clare, 2002;Hannesdottir & Morris, 2007. This deficit in error monitoring and metacognitive ability may have a considerable impact on how an individual adapts to difficulties and performs activities of daily living (Bettcher, Giovannetti, Macmullen & Libon, 2008;Giovannetti, Libon & Hart, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As explicações psicológicas (Clare, 2002) relacionam a consciência da doença em pacientes com DA às características de personalidade, mecanismos de defesa, crenças sobre saúde/doença, diagnóstico tardio, falhas ou dificuldades em iniciar o tratamento e ao conflito com os familiares/cuidadores. A perspectiva psicológica define a consciência da doença como a expressão de uma experiência que pode ser articulada pela narrativa, ou seja, o produto da interação entre a biologia e os fatores psicossociais (Clare, 2003).…”
Section: Definições De Consciência Da Doença Nos Artigos Com Fatores unclassified
“…Outra estratégia é fazer comparações desqualificando e diminuindo o problema. Tais estratégias representam formas por meio das quais os fatores psicológicos constituem-se como barreiras para a consciência da doença (Clare, 2002;2003). Esses estudos baseiam-se, principalmente, na análise qualitativa do discurso por meio de entrevistas com pacientes.…”
Section: Definições De Consciência Da Doença Nos Artigos Com Fatores unclassified
See 2 more Smart Citations